Cheikh Ibrahim Niasse (1900-1975): precursor of the Tijâniyya in Niger: doctrinal study of his thought and its social and political implications - (:unkn) unknown (My University, 2010)
Tijaniyya is one of the important Muslim brotherhoods in West Africa. The accession of Sheikh Ibrahim Niasse recessed the basics of Sufism in this part of Africa. The special feature of Faydha movement, which guide is Sheikh Ibrahim Niasse, is laid in the capacity of Tijaniyya to revivify Islam; and to consolidate spirituality which is the soul of this universal religion. The other characteristic of niassene’s movement is its suggestion to civilize all people, to give direction to young people in to Zawiyas which are real schools of life where are taught Islam values of tolerance which lauds Peace and dialogue. These values kept in secret by Sheikhs are Sufi inheritance leaved by their majors. Another difference of this movement is its adaptability and flexibility which comes mainly from Sufism assets opened up to modernity, all in saving its values. The revival is been supported by Faydha which is for now on the perfection of Tarîqa Tijaniyya on the spiritual side but also in its international importance.
Keywords: African Research